Exploring the differences between men's and women's perceptions of gender-based violence in rural Tajikistan: a qualitative study - Elizabeth A. Wood; Karina E. Wilson; K. D. Jacobs (BMC, 2021)
Abstract Background Most women living in rural provinces of Tajikistan, specifically Khatlon, experience little to no opportunities for education and economic growth, making them vulnerable to gender-based violence (GBV). Unfortunately due to social norms that are bolstered by a patriarchal society, GBV has become tolerated and even normalized in rural areas. This study looks to investigate the differences in perceptions of violence as it relates to empowerment among men and women in rural Tajikistan. Methods Data collection was done through participatory workshops and semi-structured interviews (SSI) that were led by Extension Home Economists, which lectured on gender, violence, and empowerment. Community Empowerment Drawings is a novel tool that has been used to further gather sensitive information that was not previously discussed. During this process, participant groups were asked to draw their perception of empowered versus disempowered women, later explaining the different characteristics and traits of both. Random participants across both genders were later contacted for a SSI to triangulate the data from the participatory workshops. This qualitative study implemented qualitative content analysis to explore the data inductively. Analysis of the drawings and transcripts from the workshops and SSIs included two researchers coding through an iterative process. Themes were stratified by men's and women's perceptions and codebooks were compared to ensure consensus. Results Men and women from 12 villages participated in the Community Empowerment Drawings within each workshop, with 234 participants total. Results were stratified into two categories which were later broken down into notable themes: education, employment, decision-making, marital status, relationship wellness and respect, violence, mental health, and substance abuse. Major findings illustrated how disempowered women were perceived to have more exposure to men who experience alcohol abuse. This study found that differences in perceptions of empowerment between men and women remain-with men still holding onto the traditional power structure within a household and women challenging gender roles and mobility. Conclusion Future studies may find engaging communities through drawings will yield more information regarding sensitive topics rather than traditional instruments. More support and advocacy are needed in areas of mental, neurological, and substance abuse disorders throughout rural Tajikistan.